2018
DOI: 10.1097/md.0000000000010628
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and management of pyogenic liver abscess

Abstract: Pyogenic liver abscess (PLA) are space-occupying lesions in the liver associated with high morbidity and mortality. The aim of this study is to review an Italian hospital experience in epidemiological, clinical patterns, and management of PLA.We performed a retrospective, descriptive case series at a single center assessing demographic characteristics, presentation patterns, etiological factors, microbiological etiology, and management for patients treated for PLA between 2000 and 2016.Around 109 patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
164
7
17

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(208 citation statements)
references
References 27 publications
20
164
7
17
Order By: Relevance
“…In this study mean leukocyte count was 15.790±7.173 in pyogenic abscess in contrast to amoebic liver abscess 9.184±2.372 with a significant p value of <0.0001. This finding of higher leukocyte count in pyogenic liver abscess was in agreement to study conducted by Serraino C et al 23 When pus was obtained and cultured from the abscess or blood cultures from patients with pyogenic liver abscesses revealed Klebsiella pneumoniae was the dominant organism found in 28(51.85%) subjects followed by polymicrobial in 13(24.07.0%), Escherichia coli in 07(12.96%) and cryptogenic (no growth) in 06(11.11%). K. pneumoniae being a commonest culprit was also supported by different studies carried out in Asian countries like Taiwan, China, Korea, Singapore and Pakistan.…”
Section: Discussionsupporting
confidence: 93%
“…In this study mean leukocyte count was 15.790±7.173 in pyogenic abscess in contrast to amoebic liver abscess 9.184±2.372 with a significant p value of <0.0001. This finding of higher leukocyte count in pyogenic liver abscess was in agreement to study conducted by Serraino C et al 23 When pus was obtained and cultured from the abscess or blood cultures from patients with pyogenic liver abscesses revealed Klebsiella pneumoniae was the dominant organism found in 28(51.85%) subjects followed by polymicrobial in 13(24.07.0%), Escherichia coli in 07(12.96%) and cryptogenic (no growth) in 06(11.11%). K. pneumoniae being a commonest culprit was also supported by different studies carried out in Asian countries like Taiwan, China, Korea, Singapore and Pakistan.…”
Section: Discussionsupporting
confidence: 93%
“…DM can also cause systemic metabolic disorders and impaired immunity, which weakens the ability of the liver to clear bacteria, making the bacteria easy to colonize and multiply to form abscesses [11]. Studies have confirmed that although the incidence of DM in PLA patients is [7,[12][13][14]. Even in PLA patients caused by Klebsiella pneumonia, the incidence of DM is higher as 49.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, leukocytes count showed a higher abnormal at admission in the Non-DM group, which might be related to the heavier inflammatory status in this group. Bacterial culture revealed that Klebsiella pneumonia and Escherichia coli were still the two most common infectious pathogens, whether or not combined with DM [6,12,19]. Interestingly, pus culture results illustrated 2 cases of Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of better results with PCD has also been noted by others. 1,15 There are certain advantages with PCD. These include single time skin puncture, placement of a catheter for further lavage of abscess cavity, monitoring of the cavity content etc.…”
Section: Discussionmentioning
confidence: 99%